Grado de Gingivitis en Pacientes con Tratamiento Ortodóntico en el Consultorio Dental Happy Dent - Ayacucho, 2024. - Palomino Onofre, Miguel Ángel (Universidad Privada de Huancayo Franklin Roosevelt, 2024)
El objetivo de la presente investigación fue determinar el grado de gingivitis en pacientes con tratamiento ortodóntico en el consultorio dental Happy Dent, Ayacucho – 2024. Se utilizó el método científico, nivel descriptivo, transversal y prospectivo. La muestra fue conformada por 71 pacientes con tratamiento ortodóntico. El sexo masculino presentó una mayor prevalencia de gingivitis, en el rango de edad de 18 a 28 años se logró evidenciar que el 52.4% presentó una mayor prevalencia de gingivitis, según la lateralización dentro de los pacientes zurdos; se evidenció que el 58.3% presentó una mayor prevalencia de gingivitis moderada y por último dentro del tiempo de tratamiento ortodóntico, donde los pacientes con un grado menor a 3 años de tratamiento, presentaron un mayor grado de gingivitis severa. En conclusión, se describe que el grado de gingivitis fue del 100% en los pacientes con tratamiento ortodóntico en el consultorio.

The objective of the present investigation was to determine the degree of gingivitis in patients undergoing orthodontic treatment at the Happy Dent dental office, Ayacucho - 2024. The scientific, descriptive, cross-sectional and prospective method was used. The sample consisted of 71 patients with orthodontic treatment. The male sex presented a higher prevalence of gingivitis, in the age range of 18 to 28 years it was evidenced that 52.4% presented a higher prevalence of gingivitis, according to the lateralization within the left-handed patients; it was evidenced that 58.3% presented a higher prevalence of moderate gingivitis and finally within the time of orthodontic treatment, where patients with a degree of less than 3 years of treatment, presented a higher degree of severe gingivitis. In conclusion, it is described that the degree of gingivitis was 100% in patients with orthodontic treatment in the office.
Degree of Gingivitis in Patients with Orthodontic Treatment at Happy Dent Dental Office - Ayacucho, 2024.
Keywords: Gingivitis; Ortodoncia; Grado; http://purl.org/pe-repo/ocde/ford#3.02.14